Aspectos reprodutivos e produtivos de vacas da raça holandesa e expressão gênica endometrial de receptores tipo "toll" e -defensina 5 após o parto - Telma da Mata Martins (2010)
Holstein females, from first to third lactation (n = 103), were submitted to endometrial biopsies between six and 12 hours postpartum, in order to compare the gene expression of toll-like receptors (TLRs) 1/6, 2, 4 and 5, and -defensin 5, in cows with or without uterine infection later. Animals were monitored until 42 days postpartum through rectal palpation, ultrasonography and vaginoscopy. The incidence of twin births, assisted births and retained placenta were 11.7%, 20.4% and 38.8%, respectively, and 64% of cows had metritis and/or endometritis. The uterine involution, the first detection of the corpus luteum and the first artificial insemination occurred, on average, 33.5 ± 11.1, 43.6 ± 21.5 and 75.9 ± 31.0 days postpartum, with significant differences (P<0.05) between cows with or without uterine infection. The conception rate to first service was 20.7%. Milk production was, on average, 27.9 ± 7.3 liters/day. Twenty pluriparous cows, ten with normal postpartum (group 1) and ten with retained placenta and uterine infection (group 2), were selected for gene expression studies through real-time PCR. The gene expression for all considered immune-mediated did not differ between groups. The uterine involution was correlated (P<0.05, r>0.60) to the expression of TLR4, however, no relationship was verified between uterine infections and TLRs and -defensin 5